A possible strategy for the economic restructuring of a rural region based on wine tourism: Case study of Blue Mountains, Moravia - Vaishar, Antonín; Šťastná, Milada (Hungarian Geographical Bulletin, 2025)
The article deals with the restructuring of a region focused on intensive agriculture at a time when agriculture ceases to be a source of wealth. It explores the possibilities of using tourism in an area with a high proportion of arable land without neither significant historical heritage nor natural attractions. The study method is a complex geographical analysis that determines the conditions under which the transformation of the micro region takes place. This analysis results in an overview of the microregion’s most significant strengths and weaknesses, opportunities and threats. The applied solution is the use of a specific brand, using the significant presence of wine culture. The use of this brand for marketing is presented. The increase in competition ability is based on the introduction of the idea to promote the area under the brand Blue Mountains and the use of other ideas that significantly differentiate the studied region from its neighbours. The key prerequisites are the cooperation of the actors. The main contribution of the article lies in the study of local experiences with tourism promotion and place marketing as one of the possibilities for transformation into a post-productive economy.